In vitro and in vivo Effect of Exogenous Farnesol Exposure Against Candida auris - Nagy, Fruzsina; Vitális, Eszter; Jakab, Ágnes; Borman, Andrew M.; Forgács, Lajos; Tóth, Zoltán; Majoros, László; Kovács, Renátó (Frontiers in Microbiology, 2020)
The spreading of multidrug-resistant Candida auris is considered as an emerging global health threat. The number of effective therapeutic regimens is strongly limited; therefore, development of novel strategies is needed. Farnesol is a quorum-sensing molecule with a potential antifungal and/or adjuvant effect; it may be a promising candidate in alternative treatment against Candida species including C. auris. To examine the effect of farnesol on C. auris, we performed experiments focusing on growth, biofilm production ability, production of enzymes related to oxidative stress, triazole susceptibility and virulence. Concentrations ranging from 100 to 300 uM farnesol caused a significant growth inhibition against C. auris planktonic cells for 24 hours (p<0.01-0.05). Farnesol treatment showed a concentration dependent inhibition in terms of biofilm forming ability of C. auris; however, it did not inhibit significantly the biofilm development at 24 hours. Nevertheless, the metabolic activity of adhered farnesol pre-exposed cells (75 uM) was significantly diminished at 24 hours depending on farnesol treatment during biofilm formation (p<0.001-0.05). Moreover, 300 uM farnesol exerted a marked decrease in metabolic activity against one-day-old biofilms between 2 and 24 hours (p<0.001). Farnesol increased the production of reactive species remarkably, as revealed by 2’,7’-dichlorofluorescein (DCF) assay (3.96±0.89 [nmol DCF (OD640)-1] and 23.54±4.51 [nmol DCF (OD640)-1] for untreated cells and farnesol exposed cells, respectively; p<0.001). This was in line with increased superoxide dismutase level (85.69±5.42 [munit (mg protein)-1] and 170.11±17.37 [munit (mg protein)-1] for untreated cells and farnesol exposed cells, respectively; p<0.001), but the catalase level remained statistically comparable between treated and untreated cells (p>0.05). Concerning virulence-related enzymes, exposure to 75 uM farnesol did not influence phospholipase or aspartic proteinase activity (p>0.05). The interaction between fluconazole, intraconazole, voriconazole, posaconazole, isavuconazole and farnesol showed clear synergism (FICI ranges from 0.038 to 0.375) against one-day-old biofilms. Regarding in vivo experiments, daily 75 uM farnesol treatment decreased the fungal burden in an immuncompromised murine model of disseminated candidiasis, especially in case of inocula pre-exposed to farnesol (p<0.01). In summary, farnesol shows a promising therapeutic or adjuvant potential in traditional or alternative therapies such as catheter lock therapy.